Jovens homossexuais masculinos, internet e promoção de saúde: desafios em assumir e revelar a orientação sexual - Defendi, Edson Luiz (2019)
This Doctoral Thesis focused on studying the interface between the challenges of young male homosexuals in relation to assume and reveal homosexuality, and the internet as a potential resource for health promotion to these challenges. For this purpose, a mixed method organized into three segments was used. The first consisted of a documentary search of the material coming from the first search page on Google Web, with the terms "Assuming homosexuality", "Gay acceptance", "Coming out of the closet" and "Telling that I am gayu resulting in 617 posts from 30 sites. The thematic analysis showed demands such as: vent; share feelings; diversity of revelation experiences. The interactions between homosexuals, laymen and specialists, were predominantly about receiving guidance and support, as content discussed online in forums or chats contribute to deconstruct myths about homosexuality and provide psychosocial support to potential users. The second study sought to understand the challenges and experiences of these young people by identifying themes associated with vulnerability and protection related to the assumption of sexual identity and social revelation. A qualitative-descriptive research was conducted, through a Focal Group, with seven young male homosexuals, aged between 18 and 24 years, living in the metropolitan region ofthe City of São Paulo. The results pointed out the feeling of fear as a common denominator and one of the main challenges in assuming homosexuality for themselves and in different social contexts. Assuming and revealing homosexuality has been facilitated by greater social tolerance, representativeness and information from the internet, conferring feelings of belonging and self-acceptance. Revealing homosexuality requires constant analysis and reflection, and the greatest challenge remains the revelation to the family of origin. It was concluded that revealing and assuming homosexuality brings a sense of relief and psychological well-being, reduces fear, contributing to dampen stressors and confer quality of life to young homosexuals. The third study dealt with an academic essay based on a documentary survey of internet content, aiming to evaluate the quality of online information about the challenges of young homosexuals in relation to assuming to socially reveal homosexuality. Two English-language online contents were analyzed which presented comprehensiveness and accuracy, as well as security and usability aspects for users in general. In Portuguese language, the supply of online content for the demand of young gays is incipient with only one site that presented a good range of information and content. In general, the interconnection between the three studies highlights the importance of using the internet to develop content on the challenges of young homosexuals and that this resource can increase interventions and psychosocial support in a perspective of health promotion and psychological well-being